Women's Narratives in Reading Multicultural Subjectivities: An Academic Discourse - Talukdar, Susmita (Literary Studies, 2023)
‘Difference’ in multicultural America is confusing to me as its concept determines some visible physiological features of people, and ‘knowledge’ of their history/culture, which is naturalized, circulated, and practiced through cultural institutions. Identity politics plays crucial role in its deliberate categorization and hierarchization of American subjects, which continues the historical process of separation through racism, sexism, and homophobia. As a university teacher, I have found how through the cultural institutions of university a mono-cultural population of American subjects is produced through multicultural demographic. If the primary object of multiculturalism is celebration of ‘difference,’ what ‘differences’ are celebrated most, and based on what criteria? For better understanding of ‘difference’ we should go beyond the academically sanctioned ‘Knowledge’ that disqualifies some ‘other’ knowledges, and it is by exploring some marginalized narratives of women we can reformulate the notion of ‘difference,’ that would add to the richness of ‘difference’ in multicultural discourse. Moreover, in traditional academic discourse, women’s narratives, particularly on motherhood, are less explored to finding out how they contribute to the varieties of multicultural subjectivities. My paper is based on Mahasweta Devi’s “Breast-Giver” (Standayini in original) in re-formulating a different concept of mother in its investigation on how discourses, being practiced as ‘ideologies’ through institutions, affect individuals. I propose different teaching-learning classroom activities in encouraging students to develop new perspectives of the world to modify the notion of multiculturalism that would accommodate any 'difference.'